PENINGKATAN HASIL BELAJAR SISWA MELALUI IMPLEMENTASI LANGKAH POLYA POKOK BAHASAN SISTEM PERSAMAAN LINIER DUA VARIABEL (SPLDV) PADA SISWA KELAS VIIIB SEMESTER GANJIL MTs AL-MANSYURATI NW AIK BUKAK TAHUN PELAJARAN 2015/2016 - Pujilestari Pujilestari (Lembaga Penelitian dan Pendidikan Mandala, 2016)
The problems that arise during observation learning mathematics grade VIII MTs Al-Mansyurati NW Aik Bukaq that learning is less effective because learning activities do vary and the discussions in the classroom are still rare. This will affect student learning outcomes. To overcome these problems, researchers applied learning with Polya method. The purpose of this action research is to determine how much increase in mathematics learning outcomes in grade VIII MTs Al-Mansyurati NW Aik Bukak in academic year 2015/2016. This type of research is a classroom action research, which in the implementation of this study using several cycles. The research instrument used in this study is the observation sheets, worksheets, and a test sheet. This research was conducted at MTs Al-Mansyurati NW Aik Bukak. The subjects of this study is grade VIIIB consisting of 25 students. In cycle I students learning activity score is 13.33 with less active category, while the average value of student learning outcomes is 73.75 with the percentage of classical completeness amounted to 83.33%. In cycle two student activity score is 23.50 with a very active category, while the average value of student learning outcomes is 79.29 with the percentage of 91.67% classical completeness. By looking at the percentage of students in the classical learning completeness has achieved the expected indicators. Thus it can be concluded that the implementation of measures to improve learning outcomes eighth grade students of MTs Al-Mansyurati NW in the academic year 2015/2016